2003
DOI: 10.1103/physrevb.67.125321
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium morphologies for Cl-roughened Si(100) at 700–750 K: Dependence on Cl concentration

Abstract: Adsorbed halogen atoms on Si͑100͒-͑2ϫ1͒ can induce roughening at temperatures where material removal ͑etching͒ is minimal. Variable temperature scanning tunneling microscopy was used to follow roughening at 700-750 K for surfaces with 0.1-0.99 ML of Cl. Dimer vacancies and Si adatoms were observed at short times, and at longer times the progression toward a state of dynamic equilibrium was traced. Once dynamic equilibrium was reached, the appearance of individual pits and regrowth islands changed but their den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Simulations outcomes are more consistent with the experimental morphology reported in Ref. [14] showing large pits and regrowth islands at low coverages.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Simulations outcomes are more consistent with the experimental morphology reported in Ref. [14] showing large pits and regrowth islands at low coverages.…”
Section: Resultssupporting
confidence: 92%
“…B shows an adsorbate particle that affects substrate interactions among grey substrate particles. C depicts an adsorbate interacting stronger with the substrate at a step [14], the width of simulated island and pit features are typically of only 1-2 dimer rows. In equilibrium, most Cl atoms on Si(100) are paired forming filled dimers that, due to steric repulsions, would spread on the surface to reduce the total system energy.…”
Section: Resultsmentioning
confidence: 99%
“…The 2s peak was used to compute the Cl coverage because its baseline was better defined than that of the 2p peaks. Only samples with initial C coverages <0.1 ML were used to compute the average, since Cl atoms react with C. Scanning tunneling microscopy (STM) showed that coverages up to 1 ML are produced by annealing to 1100-1500 K in ultrahigh vacuum (UHV) to obtain a Si(1 0 0)-(2 · 1) structure and dosing the halogen using an electrochemical cell [23,41]. The lower saturation coverage produced by liquid cleaning and UV-Cl 2 treatment could be the result of an inaccurate coverage estimate based on the Cu reference standard or due to the chemical rather than thermal process used to prepare the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The tetrahedral bonding in the diamond cubic structure leads to dimer row reconstructions of (100) surfaces and uniaxial strain on (100) terraces. As a result, growth on, and etching of, these surfaces typically leads to elongated islands and pits, 32,33,36,44 accounting for the alkaline earth-induced formation of trenches and elongated plateaus rather than square islands. 36 The trench edges can be viewed as essentially step edges.…”
Section: Discussionmentioning
confidence: 99%
“…32 Compared to the clean Ge(100) surface characterized by equally spaced monatomic steps, 30 it is evident that the Sr has drastically altered the step-terrace structure of the Ge surface. The formation of elongated Ge islands can be explained by either Sr etching away the Ge terraces, 33 or Sr penetrating the surface layer and displacing Ge atoms, or dimers, which then diffuse across the surface and nucleate islands. 34 The appearance of small Ge islands on the upper terrace towards the bottom right of Fig.…”
Section: B Atomic-scale Structural and Morphological Changes Inducedmentioning
confidence: 99%